2022
DOI: 10.1007/s12311-022-01379-3
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Neuron Navigator 2 Impairs Brain and Cerebellar Development

Abstract: Cerebellar hypoplasia and dysplasia encompass a group of clinically and genetically heterogeneous disorders frequently associated with neurodevelopmental impairment. The Neuron Navigator 2 (NAV2) gene (MIM: 607,026) encodes a member of the Neuron Navigator protein family, widely expressed within the central nervous system (CNS), and particularly abundant in the developing cerebellum. Evidence across different species supports a pivotal function of NAV2 in cytoskeletal dynamics and neurite outgrowth. Specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Furthermore, granule cell migration was impaired in hypomorphic cerebella in vivo, and migration and neurite outgrowth defects were observed in cerebellar explants from the knockout mice (McNeill et al, 2011). A more recent paper also observed a reduction of cerebellar size in these mice, including abnormalities in the development of the VIa and VIb/VII lobes, as well as a thin corpus collosum, and size reduction in the thalamus and hypothalamus (Accogli et al, 2022). All of these phenotypes demonstrate that Nav2 plays an essential role in neuron migration and morphogenesis of several areas of developing brain.…”
Section: Functions Of the Navigators Insights From Mouse Modelsmentioning
confidence: 92%
See 4 more Smart Citations
“…Furthermore, granule cell migration was impaired in hypomorphic cerebella in vivo, and migration and neurite outgrowth defects were observed in cerebellar explants from the knockout mice (McNeill et al, 2011). A more recent paper also observed a reduction of cerebellar size in these mice, including abnormalities in the development of the VIa and VIb/VII lobes, as well as a thin corpus collosum, and size reduction in the thalamus and hypothalamus (Accogli et al, 2022). All of these phenotypes demonstrate that Nav2 plays an essential role in neuron migration and morphogenesis of several areas of developing brain.…”
Section: Functions Of the Navigators Insights From Mouse Modelsmentioning
confidence: 92%
“…Previous studies found that Navigators and their invertebrate homologs have AAA+ nucleotide triphosphatase (NTPase), calponin homology (CH), and coiled-coil (CC) domains, with the exception that NAV1 lacks the CH domain, likely due to secondary loss ( Maes et al, 2002 ; Peeters et al, 2004 ; Stringham and Schmidt, 2009 ; Abe et al, 2014 ; Accogli et al, 2022 ). However, those differ in the number of reported CC domains (2, 3, or 4), and in the reported presence or absence of conserved microtubule- or cytoskeletal-binding domains.…”
Section: Navigators Have Conserved Domains and Extensive Disordered R...mentioning
confidence: 99%
See 3 more Smart Citations